Neoliberal dönüşüm sürecinde Türkiye'de sosyal politikalar : Aile ve Sosyal Politikalar Bakanlığı - Polat Ber, Gönül (My University, 2023)
Neoliberal dönüşüm sürecinde sosyal politikalar sermaye birikiminin yeni değerlenme alanlarından biri haline dönüştürülürken, aynı zamanda emekçiler ile diğer toplumsal kesimleri koruyan nitelikleri olumsuz yönde yeniden yapılandırılmıştır. Bu çalışmanın amacı, neoliberal dönüşüm sürecinde sınıfsal eşitsizlikler temelinde büyüyen işsizlik, yoksulluk ve sosyal güvencesizlik şeklindeki sorun alanlarına müdahale etme ve yönetme politikalarının, sosyal politikaların, uluslararası alandan ulusal düzeye, Aile ve Sosyal Politikalar Bakanlığı somutunda incelenmesidir. Çalışmada literatür taraması ile Aile ve Sosyal Politikalar Bakanlığı ve ilgili diğer kurum ve kuruluşların belge ve raporları gibi ikincil kaynaklardan yararlanılmıştır. Türkiye’de var olan sosyal politika uygulamaları toplum aleyhine geriye çekilirken, bunun yerine konulmaya çalışılan politikaların anlam ve işlevleri uluslararası “yeni sosyal politika” hedefleriyle uyumlu yürüyen süreçleri içermiştir. Çalışmada, Aile ve Sosyal Politikalar Bakanlığının, “çalışma” ve “hak” temelli kavramlar dışında gelişen uluslararası “yeni sosyal politika” anlayışının, Türkiye’nin “aile”, “hayırseverlik”, “klieantalizm” gibi sosyal ve siyasal özgünlükleriyle buluşturulmasında önemli bir misyona sahip olduğu bulgularına ulaşılmıştır.

Within the process of neoliberal transformation, social policies were transformed into a new valuation area of capital accumulation and at the same time their qualities that protect laborers and other parts of the society were restructured in a negative way. The aim of this study is to examine the policies of intervention and governing the problems such as unemployment, poverty and social insecurity that increased on the basis of class inequalities during the neoliberal transformation process, within the scope from international to national, and in the context of the Ministry of Family and Social Policies. This study uses the data gathered through the literature review and the examination of the published documents and reports of the Ministry of Family and Social Policies and the relevant institutions and organizations. While the existing social policy practices in Turkey were restrained for the disadvantage of the society, the meaning and functions of the policies that were tried to be replaced included processes that were compatible with the international new social policy goals. In this study, we came to the conclusion that the Ministry of Family and Social Policies had an essential role in combining this international “new social policy” understandings that emerged apart from the concepts of “work” and “right” with Turkey’s authenticities of such as “family”, “charity”, “clientalism”.
Social policies in Turkey during neoliberal transformation : The Ministry of Family and Social Policies
Keywords: Aile ve Sosyal Politikalar Bakanlığı; Capital Accumulation; Democracy; Demokrasi; Economic conditions; Ekonomik durum; Ministry of Family and Social Policy; Neoliberal Policies; Neoliberal Politikalar; Neoliberalism; Neoliberalizm; Politics and government; Sermaye Birikimi; Sınıf Mücadelesi; Siyaset ve yönetim; Social Policies; Social Policies in Turkey; Sosyal Politikalar; Turkey; Türkiye; Türkiye’de Sosyal Politikalar